1947
DOI: 10.1002/jctb.5000661107
|View full text |Cite
|
Sign up to set email alerts
|

The determination of columbium in rustless and heat‐resisting steels. Part II. A co‐operative examination of some of the methods available

Abstract: Results are given of a co‐operative examination of several methods of determining columbium in 18% Cr/8% Ni, rustless steels by six laboratories. Various features of the methods are discussed and the order of agreement obtained by different laboratories working independently is shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1949
1949
1964
1964

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The final residue of oxide of columbium, tantalum, and titanium was weighed and the titanium content was determined colorimetrically. Craven (69) reported the results of a cooperative examination of this and other methods. He concluded that while four procedures gave satisfactory results, the method of Bagshawe and Elwell (13) was the best.…”
Section: Zirconium and Hafniummentioning
confidence: 99%
“…The final residue of oxide of columbium, tantalum, and titanium was weighed and the titanium content was determined colorimetrically. Craven (69) reported the results of a cooperative examination of this and other methods. He concluded that while four procedures gave satisfactory results, the method of Bagshawe and Elwell (13) was the best.…”
Section: Zirconium and Hafniummentioning
confidence: 99%